Myocardial infarction with nonobstructive coronary arteries due to acute coronary vasospasm induced by toripalimab: a case report and review of literature - Huang, Bihan; Chen, Shaoyuan; Zhang, Haigang; Han, Xueying (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCoronary artery spasm (CAS), one of the etiologies for MINOCA, is an uncommon cause of acute chest pain. Toripalimab, a recombinant monoclonal antibody targeting programmed death receptor 1 (PD-1), exhibits a wide range of anti-tumor activities. Nevertheless, instances of toripalimab-induced cardiotoxicity have been seldom reported.MethodsWe present the case of a 60-year-old male patient diagnosed with hepatocellular carcinoma who experienced MINOCA subsequent to the administration of toripalimab. Based on the patient's symptoms, electrocardiogram (ECG) findings, and coronary angiography, transient occurrence CAS was established. The patient was prescribed diltiazem sustained-release capsules. During his follow-up on an outpatient basis, he did not experience a recurrence of the previously reported chest discomfort or any other symptoms. We used the CARE checklist when writing our report.ConclusionThis is the first case report of MINOCA induced by toripalimab, mediated through coronary artery spasm. This case report emphasizes the awareness regarding the potential for severe cardiovascular complications associated with the administration of toripalimab.